SOCIAL MEDIA AS A PLATFORM FOR CONTEMPORARY PERFORMANCE AND VISUAL CULTURE - R, Jeevajothi; J, Monish; V, Shanthi; N, Koushik Kumar; T, Veda Vijaya; Xueyi, Fang (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The growing popularity of social media platforms has greatly changed the environment of modern performance and visual culture. Online spaces like social network sites and multimedia sharing sites have emerged to be fluid environments of artistic creation, distribution, and communication. The work examines the way social media is used as a participatory space of the modern day performance and visual culture, where artists are able to market creative work out of the gallery and physical performance space. The study reviews the conceptual correlation between digital media and artistic communication as to how the online media supports real time performances, participatory culture, as well as communication with audiences around the globe. The paper also examines the role of the major platforms in sustaining visual storytelling with short-form content, live stream, and content circulation via algorithms, which affect the perception and exposure of artistic work. As new opportunities are offered by social media in terms of accessibility and creative experimentation, a number of problems are raised, such as the problem of intellectual property, authenticity, digital manipulation, and privacy of information. The research evaluates the new role of social media in the development of contemporary artistic practices through the case study of various examples of digital performance art, virtual exhibitions, and social media campaigns in the visual arts.